South to the Sun, North to the Earth: Maps within and beyond the Narrative - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2018)
[only abstract in English; full article and abstract in Lithuanian] This article discusses the relationship that occurs between a map and a narrative. As a mean of visualization, a map is used in varied contexts, where it is usually interpreted as a representation of a certain territory, both real and fictitious. The dependence on temporality and a multitude of possible layers (multifacetedness) reveal that no map can represent any single territory completely. If the only aim of any map is as precise as a representation of a certain space as possible, then cartography becomes a never-ending, unrealizable and futile activity. Though a map cannot be reduced to a mere representation, it tells stories that alternatively justify its existence. Therefore, it is important to answer the following: what is the epistemological status of map? Is a “mute” map possible? Are there any unmappable narratives? As an illustration of the narrative nature of the map, the Atlas of Russian History by George Maciunas is provided and analyzed.